Anticonvulsant and sedative–hypnotic activity screening of pearl and nacre (mother of pearl). (2nd April 2016) - Zhang, Jing-Xian; Li, Shang-Rong; Yao, Shuai; Bi, Qi-Rui; Hou, Jin-Jun; Cai, Lu-Ying; Han, Su-Mei; Wu, Wan-Ying; Guo, De-An
Abstract: Ethnopharmacological relevance: Pearl and nacre are valuable traditional medicines to treat palpitations, convulsions or epilepsy in China for thousands of years. However, the active ingredients are not clear till now. Aim of the study: The main purpose of the current investigation was to assess the anticonvulsant and sedative–hypnotic activity of pearl powder and nacre powder, including their corresponding 6 protein extracts. Material and methods: Determination of the amino acid composition of the obtained protein was carried out by ultra-performance liquid chromatography (UPLC) combined with 6-aminoquinolyl- N -hydroxysuccinimidyl carbamate (AQC) pre-column derivatisation. The influence of the tested drugs on locomotor activity and convulsions latency was recorded. The contents of 5-Hydroxytryptamine (5-HT) and γ -aminobutyric acid (GABA) in brain were detected by enzyme-linked immunesorbent assay (ELISA) kits. In addition, immunohistochemistry was carried out to evaluate the changes of 5-HT3 and GABAB . In parallel, the expressions of them were demonstrated by western blot. Results: The obtained data suggested that pearl original powder (1.1 g/kg), pearl water-soluble protein (0.2 g/kg), pearl acid-soluble protein (0.275 g/kg), pearl conchiolin protein (1.1 g/kg), nacre original powder (1.1 g/kg), nacre water-soluble protein (0.2 g/kg), nacre acid-soluble protein (0.7 g/kg) and nacre conchiolin protein (1.1 g/kg) could down-regulate the expression of 5-HT3 and up-regulate the level of GABAB to varying degrees compared with the control group. Besides, drug administration also reduced the locomotor activity and increased convulsions latency with a certain mortality. Conclusions: These findings correlated with the traditional use of pearl and nacre as sedation and tranquilization agents, thus making them interesting sources for further drug development and also providing critical important evidence for the selection of quality control markers. Graphical abstract: